The current role of dendritic cells in the progression and treatment of colorectal cancer - Zhang, Yuanci; Ji, Songtao; Miao, Ge; Du, Shuya; Wang, Haojia; Yang, Xiaohua; Li, Ang; Lu, Yuanyuan; Wang, Xin; Zhao, Xiaodi (Cancer biology & medicine, 2024)
Colorectal cancer (CRC) is the third most common cancer and the second leading cause of cancer-related deaths worldwide. Dendritic cells (DCs) constitute a heterogeneous group of antigen-presenting cells that are important for initiating and regulating both innate and adaptive immune responses. As a crucial component of the immune system, DCs have a pivotal role in the pathogenesis and clinical treatment of CRC. DCs cross-present tumor-related antigens to activate T cells and trigger an antitumor immune response. However, the antitumor immune function of DCs is impaired and immune tolerance is promoted due to the presence of the tumor microenvironment. This review systematically elucidates the specific characteristics and functions of different DC subsets, as well as the role that DCs play in the immune response and tolerance within the CRC microenvironment. Moreover, how DCs contribute to the progression of CRC and potential therapies to enhance antitumor immunity on the basis of existing data are also discussed, which will provide new perspectives and approaches for immunotherapy in patients with CRC.